The ecology and distribution of Aleppo pine forests in the upper Ionian coast in the province of Cosenza (Calabria) - Aramini G.; Ciancio O.; Iovino F.; Menguzzato G.; Nicolaci A.; Nocentini S.; Paone R. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
Aleppo pine is a species found primarily in the western sector of the Mediterranean basin. In Calabria, natural pine forests are found in the upper Ionian district. The presence of Aleppo pine in this part of Calabria is related to the ecology of the species and specifically its xerophilous and hardy nature, which is suited to the pedoclimatic conditions that characterize the area. The aim of this paper is to analyze the ecological factors that affect the current distribution of Aleppo pine in the far north eastern part of Calabria (Upper Ionian Coast in the Province of Cosenza), in order to characterize the area's environmental peculiarities, by highlighting those with the greatest significance for the species. The analysis of the distribution of Aleppo pine forests, along with the results of the pedological surveys and study of the climatic conditions brought to light some peculiar aspects of the ecological context in which the species grows and where the Aleppo pine stands comprise a typical element of the forest landscape in the area.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)